2006
DOI: 10.1111/j.1365-2494.2006.00525.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive tillers in cut tall fescue swards: differences according to sward age and fertilizer nitrogen application, and relationships with the local dynamics of the sward

Abstract: The effects of sward age and fertilizer-nitrogen (N) application rate on reproductive tillers and their involvement in the dynamics of swards of perennial grasses were investigated using sown swards of tall fescue (Festuca arundinacea). Treatments included plots representing two sward ages (two and six-year-old swards) and two fertilizer-N rates (150 and 350 kg N ha )1 yr )1 ) on the same experimental field. In each of 2 years all plots were cut at the silage stage and three times afterwards. After each cut, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 32 publications
1
13
0
1
Order By: Relevance
“…The combined proportion of ELONG and GEN tillers (51–69% on the last two sampling times) in the regrowth of our study is therefore comparable to that reported by Bélanger and McQueen (1998) for nonlimiting N conditions. The proportion of GEN tillers in the primary growth (10–24%) of tall fescue is consistent with values reported from other studies (5–15%) (Lafarge, 2006).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The combined proportion of ELONG and GEN tillers (51–69% on the last two sampling times) in the regrowth of our study is therefore comparable to that reported by Bélanger and McQueen (1998) for nonlimiting N conditions. The proportion of GEN tillers in the primary growth (10–24%) of tall fescue is consistent with values reported from other studies (5–15%) (Lafarge, 2006).…”
Section: Resultssupporting
confidence: 91%
“…The proportion of GEN tillers can be affected by N fertilization. Nitrogen fertilization increased the proportion of GEN tillers in the spring growth of tall fescue (Lafarge, 2006). In the regrowth of timothy, the proportion of GEN tillers increased from 10% with no N applied to 51% under nonlimiting N conditions (Bélanger and McQueen, 1998).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant carbohydrate status is well known to affect tillering, therefore indices of carbohydrate supply/demand have been developed to account for how this factor modulates tillering under field conditions (Kirby et al . ; Lafarge ; Luquet et al . ; Kim et al .…”
Section: Introductionmentioning
confidence: 99%
“…Seedheads/m 2 averaged 117 and 475 in 2003 and 2004, respectively. This compares to a range of 300 to 600 in France (9), 388 for ‘Fawn’ grown in Oregon (19), and 180 seedheads/m 2 for winter clipped ‘AU Triumph’ in Alabama (15).…”
Section: Winter Grazing Effects On Seed Yield Components and Germinationmentioning
confidence: 88%